Grammaire fonctionnelle (de discours) : Évaluation et perspectives - Jadir, Mohammed (HERMES - Journal of Language and Communication in Business, 2009)
This article is, ﬁrst, concerned with the presentation and evaluation of the most representative contributions of the development of the current, sentence-oriented Functional Grammar (FG) model into a more discourse-oriented one (Connolly et al. 1997, Hannay/Bolkestein 1998, Mackenzie/Gómez-González 2004, etc.). The two particularly emphasized approaches to extend the model are upward layering approach (e.g. Dik 1997a,b, Hengeveld 1997, Moutaouakil 1998, Jadir 1998) and modular approach (Kroon 1997, Vet 1998, Bolkestein 1998). Then, starting from “structural parallel” proposals (Rijkhoff 1990, 1992; Moutaouakil 1999, 2000), I will argue that the “increasing parallel” hypothesis requires the integration of the ‘expanding’ and the modular approaches. Finally, I will survey the recent researches carried out within FG framework (Mackenzie 2000, 2004; Hengeveld 2004a,b; Hengeveld/Mackenzie 2006) for which a more adequate model of Functional Discourse Grammar should be hierarchical and modular.